Pengaruh Religiusitas terhadap Berpikir Positif pada Kelompok Pengajian di Desa Koto Petai Kabupaten Kerinci - Ahmad Zuhdi; Zuwirda Zuwirda (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This research is based on the phenomena in Koto Petai Village where the people are classified as religious but still not able to apply positive thinking patterns. This study uses a quantitative method with the type of associative research in the form of a causal relationship. The population in this study were members of the Majlis Ta'lim Tarbiyatul Islamiyah study group, Ahlussunnah wal Jamaah and Middle Group totaling 182 people. Sampling with purposive sampling specific nonprobability sampling technique with a sample of 117 people. Data was collected with a Likert scale model, namely the scale of religiosity and scale of positive thinking. Based on the results of the study it was found (1) Tarbiyatul Islamiyah have a high level of religiosity (about 66.7%), Ahlussunnah wal Jamaah have a high level of religiosity (about 59.6%), and Middle Group was high too (about 85.7%), (2) the level of positive thinking of members the Tarbiyatul Islamiyah study group is balanced between medium and high, which is 50.0%, the study group Ahlussunnah wal Jamaah has a moderate level of positive thinking that is 61.7%, and the Middle Group has a positive level of thinking that is 64.3%, (3) religiosity have a significant effect on positive thinking in the Tarbiyatul Islamiyah study group with R-Square value of 0.226, in the Ahlussunnah wal Jamaah study group there was no significant effect with the R-Square value of only 0.034, and in the Middle Group study group there was no influence significant with the R-Square value of only 0.055.